Genome-wide characterization of the hyperaccumulator Sedum alfredii F-box family under cadmium stress - Zhuang Zhang (Nature Portfolio, 2021)
Abstract The F-box genes, which form one of the largest gene families in plants, are vital for plant growth, development and stress response. However, F-box gene family in Sedum alfredii remains unknown. Comprehensive studies addressing their function responding to cadmium stress is still limited. In the present study, 193 members of the F-box gene (SaFbox) family were identified, which were classified into nine subfamilies. Most of the SaFboxs had highly conserved domain and motif. Various functionally related cis-elements involved in plant growth regulation, stress and hormone responses were located in the upstream regions of SaFbox genes. RNA-sequencing and co-expression network analysis revealed that the identified SaFbox genes would be involved in Cd stress. Expression analysis of 16 hub genes confirmed their transcription level in different tissues. Four hub genes (SaFbox40, SaFbox51, SaFbox136 and SaFbox170) were heterologously expressed in a Cd-sensitive yeast cell to assess their effects on Cd tolerance. The transgenic yeast cells carrying SaFbox40, SaFbox51, SaFbox136, or SaFbox170 were more sensitive and accumulated more cadmium under Cd stress than empty vector transformed control cells. Our results performed a comprehensive analysis of Fboxs in S. alfredii and identified their potential roles in Cd stress response.